2017
DOI: 10.15252/embj.201796750
|View full text |Cite
|
Sign up to set email alerts
|

Protease cleavage site fingerprinting by label‐free in‐gel degradomics reveals pH ‐dependent specificity switch of legumain

Abstract: Determination of protease specificity is of crucial importance for understanding protease function. We have developed the first gel-based label-free proteomic approach (DIPPS-direct in-gel profiling of protease specificity) that enables quick and reliable determination of protease cleavage specificities under large variety of experimental conditions. The methodology is based on in-gel digestion of the gel-separated proteome with the studied protease, enrichment of cleaved peptides by gel extraction, and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 51 publications
(85 reference statements)
7
79
1
Order By: Relevance
“…Interestingly, around 5% of vertebrate cleavage site orthologs have glutamate in the P1 position instead of aspartate (Table 1). Previous in vitro reports have shown that caspases-3, -6, and -7 are able to accommodate P1 glutamate in the active site and cleave substrates with P1 E cut sites with the same affinity but with a twofold slower rate than substrates with aspartate in the same position [13,37]. The same study by the Wells group demonstrated that substitution of P1 glutamate by aspartate actually results in a higher rate of protein cleavage by caspases.…”
Section: Vertebrate Caspase Targets Are Highly Conserved At the Levelmentioning
confidence: 90%
“…Interestingly, around 5% of vertebrate cleavage site orthologs have glutamate in the P1 position instead of aspartate (Table 1). Previous in vitro reports have shown that caspases-3, -6, and -7 are able to accommodate P1 glutamate in the active site and cleave substrates with P1 E cut sites with the same affinity but with a twofold slower rate than substrates with aspartate in the same position [13,37]. The same study by the Wells group demonstrated that substitution of P1 glutamate by aspartate actually results in a higher rate of protein cleavage by caspases.…”
Section: Vertebrate Caspase Targets Are Highly Conserved At the Levelmentioning
confidence: 90%
“…In the second step, the protease-generated peptides can be identified with any tandem mass spectra search tool. In our implementation, we used the Andromeda 30 search engine in MaxQuant 31 using unspecific database search parameters as described elsewhere 21 . Importantly, we searched the data with a reduced database (HTPS_DB.fasta) generated from proteins identified in Trypsin, Lys-C, Asp-N, Glu-C and Chymotrypsin samples.…”
Section: A Methods For High-throughput Screening Of Protease Substratementioning
confidence: 99%
“…Relevant techniques to identify protease substrates include COFRADIC (combined fractional diagonal chromatography) 10,11 , ChaFraDIC (charge-based fractional diagonal chromatography) 12 , PICS (proteomic identification of protease cleavage sites) 13,14 and TAILS (terminal amine isotopic labeling of substrates) 15,16 which are reviewed elsewhere [17][18][19] . More recently, workflows like FPPS (fast profiling of protease specificity) 20 and especially label-free degradomic workflows like DIPPS (direct in-gel profiling of protease specificity) 21 and ChaFraTip (ChaFraDIC performed in a pipet tip format) 22 made protease characterization easier and more accessible by describing simplified workflows and omitting extensive fractionation or labeling steps. Furthermore, DIPPS 21 and ChaFraTip 22 can simultaneously map prime and non-prime substrate sites by sequencing the protease-generated peptides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four kidney samples selected as most representative from each treatment group and four control kidney samples were processed for mass spectrometry analysis as described before [79] with a slightly modified protocol. Frozen tissues were cut into pieces of about 30 mg on dry ice to prevent thawing.…”
Section: Tissue Homogenizationmentioning
confidence: 99%